Unexpected Position-Dependent Effects of Ribose G-Quartets in G-Quadruplexes - Zhou, Jun; Amrane, Samir; Rosu, Frédéric; Salgado, Gilmar F; Bian, Yunqiang; Tateishi-Karimata, Hisae; Largy, Eric; Korkut, Dursun Nizam; Bourdoncle, Anne; Miyoshi, Daisuke; Zhang, Jian; Ju, Huangxian; et al. (Journal of the American Chemical Society, 2017)
To understand the role of ribose G-quartets and how they affect the properties of G-quadruplex structures, we studied three systems in which one, two, three, or four deoxyribose G-quartets were substituted with ribose G-quartets. These systems were a parallel DNA intramolecular G-quadruplex, d(TTGGGTGGGTTGGGTGGGTT), and two tetramolecular G-quadruplexes, d(TGGGT) and d(TGGGGT). Thermal denaturation experiments revealed that ribose G-quartets have position-dependent and cumulative effects on G-quadruplex stability. An unexpected destabilization was observed when rG quartets were presented at the 5'-end of the G stack. This observation challenges the general belief that RNA residues stabilize G-quadruplexes. Furthermore, in contrast to past proposals, hydration is not the main factor determining the stability of our RNA/DNA chimeric G-quadruplexes. Interestingly, the presence of rG residues in a central G-quartet facilitated the formation of additional tetramolecular G-quadruplex topologies showing positive circular dichroism signals at 295 nm. 2D NMR analysis of the tetramolecular TGgGGT (lowercase letter indicates ribose) indicates that Gs in the 5'-most G-quartet adopt the syn conformation. These analyses highlight several new aspects of the role of ribose G-quartets on G-quadruplex structure and stability, and demonstrate that the positions of ribose residues are critical for tuning G-quadruplex properties.
Keywords: G-kvadruplexy; DNA; Nuclear Magnetic Resonance, Biomolecular; G-Quadruplexes; nukleární magnetická rezonance biomolekulární; RNA; ribosa; Ribose